2017
DOI: 10.3389/fevo.2017.00118
|View full text |Cite
|
Sign up to set email alerts
|

Harvest Regulations and Implementation Uncertainty in Small Game Harvest Management

Abstract: A main challenge in harvest management is to set policies that maximize the probability that management goals are met. While the management cycle includes multiple sources of uncertainty, only some of these has received considerable attention. Currently, there is a large gap in our knowledge about implemention of harvest regulations, and to which extent indirect control methods such as harvest regulations are actually able to regulate harvest in accordance with intended management objectives. In this perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…As a case in point, several studies have indicated that using harvest data as a proxy of population trends may be fraught with weaknesses (Ranta et al 2008, Kahlert et al 2015. Indeed, many scientists call for caution when using harvest data in management, especially when hunters' effort is not carefully monitored (Moa et al 2017, Eriksen et al 2018. Conversely, several critical comparisons of the relationship between harvest data and population change have reported strong correlations (Cattadori et al 2003, Jarnemo andLiberg 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As a case in point, several studies have indicated that using harvest data as a proxy of population trends may be fraught with weaknesses (Ranta et al 2008, Kahlert et al 2015. Indeed, many scientists call for caution when using harvest data in management, especially when hunters' effort is not carefully monitored (Moa et al 2017, Eriksen et al 2018. Conversely, several critical comparisons of the relationship between harvest data and population change have reported strong correlations (Cattadori et al 2003, Jarnemo andLiberg 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly common, for example, when quotas are specified with spatial or temporal specifications, or in terms of amounts per person. This means that decision makers need to estimate the relationship between the quota and the levels of harvest they intend to be taken (Moa, Eriksen, & Nilsen, 2017). Despite these critical assumptions, there are relatively few studies on imperfect harvest implementation in terrestrial wildlife systems ).…”
Section: S11 Model Frameworkmentioning
confidence: 99%
“…Harvest rules implemented for small game birds (grouse species) in Europe and North America are reviewed in (Moa et al, 2017). They note that proportional and threshold-proportional principles are common, however in practice bag sizes are often relatively more limited at large population sizes, against recommendations (Moa et al, 2017).…”
Section: S13 Harvest Strategies Quota Parameters and Optimizationmentioning
confidence: 99%
“…Adaptive management is designed to aid decision‐making in complex systems while providing an opportunity to increase knowledge of those systems (Williams, 2011). Adaptive management of commercially harvested game populations is common (Moa, Eriksen, & Nilsen, 2017; Ramsey et al, 2010), but do we apply the same level of rigor to conservation restoration? Under adaptive management, clear goals and quantifiable indicators of success are identified and predictive models are used to inform management actions (Lacy, 2019; Williams, 2011).…”
Section: Introductionmentioning
confidence: 99%